Sundanese Short Story (Carpon) as an Effort to Improve Reading Ability of Middle School Students - Ababil, Salza Nabila; Muktiarni, M.; Mupita, Jonah (Universitas Pendidikan Indonesia (UPI), 2021)
In Indonesia, the literacy level of students is still very low, especially in learning Sundanese. This research is motivated by seeing children nowadays who very rarely even forget about cultures, as well as the lack of literacy in Sundanese literary works, including short stories (known as Carpon or Carita Pondok). Therefore, we are looking for ways to increase Sundanese literacy, one of which is by getting used to reading Carpon. The purpose of this study was to find out how far the level of understanding of student literacy after reading Carpon also fosters reading interest in Carpon. This research is descriptive quantitative. The research instrument carried out was in the form of a pre-test and post-test which was carried out by distributing questionnaires (google form) to students via whatsapp groups, the source of data in this study were students of junior high school. The results showed that the pre-test results were 61% of students who answered yes, and 39% of students who answered no and in the post-test 85% of students answered yes and 15% of students answered no. It can be said that the level of student literacy and students' understanding of Carpon reading activities has greatly increased.